TINGKAT KEPUASAN MASYARAKAT TERHADAP PELAYANAN PENGGALIAN INFORMASI SWAMEDIKASI OLEH PETUGAS APOTEK PADA MASA PANDEMI COVID-19 DI KECAMATAN TUAH MADANI KOTA PEKANBARU TAHUN 2021 - Putri Zulnandita; Fina Aryani; Rahayu Utami; Mustika Furi; Septi Muharni (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Self-medication is an effort made to overcome complaints or pain by using medicines purchased without a doctor's prescription. One of the stages in this self-medication is extracting information. Information gathering aims to collect or dig up information from patients regarding the symptoms experienced by patients so that pharmacy staff are assisted in making decisions and recommending the correct therapy for patients. To determine the quality of information mining services, one way is to find out the community's satisfaction with the self-medication information mining service. Satisfaction is an important part of health services because respondent satisfaction cannot be separated from the quality of health services. The purpose of this study was to determine the level of community satisfaction with the service of extracting information on self-medication and providing drug information by pharmacists during the COVID-19 pandemic in the Tuah Madani sub-district, Pekanbaru City in 2021 based on five (5) dimensions of service quality, namely reliability, responsiveness, empathy, assurance and tangibles. This research is observational/survey research with a descriptive research design using quantitative analysis. Sampling was done by non-probability sampling method on 100 respondents. The results showed that respondents' satisfaction was in the aspect of reliability 66%, responsiveness 76.2%, empathy 74.4%, assurance 75.25% and tangibles 82.12%. This shows that the community as a whole is satisfied with the services provided by pharmacists.